Sustaining the Quality of Life for University Employees with Obesity Using Mindfulness Activities and Work Engagement: A Quasi-Experimental Design - Kadir, Nor Ba’yah Abdul; Helma, Rusyda; Ismail, Wan Nur Khairunnisa; Abdul Jalil, Siti Jamiaah; Abdullah, Nurul-Azza; Che Kasim, Arena; Mohd. Hoesni, Suzana; Manaf, Mohd Rizal Abdul (Sustainability, 2022)
Using an e-calendar, a web-based intervention program, informal mindfulness activities, and work engagement, this study evaluated the sustainability of the quality of life for staff with obesity at a Malaysian public university. The participants were identified through the human resources department of the university. The inclusion criteria required an age of 20–59 years and BMI ≥ 25. The exclusion criteria were pregnancy, the use of weight loss pills or supplements that can influence weight, chronic illness, and the use of medication that requires physician monitoring. Thirty-one university staff were assessed for quality of life using a within-subject repeated-measures design. The participants were asked to use the study website for 10 to 15 min/day for 36 weeks. Data was captured by a pretest, posttest, and two follow-up surveys. The results showed an increase in the posttest mean scores for all domains representing the quality of life. As expected, three domains increased at follow-up 1 and were maintained at follow-up 2. This suggests that informal mindfulness practices and work engagement using an e-calendar are practical means to increase and sustain the quality of life of employees. In conclusion, the quality of life among university staff with obesity can be improved using informal mindfulness activities and work engagement, and an e-calendar is another alternative method of practicing mindfulness at home and at the workplace. The implications of this study are also discussed.